Understanding Fencing Offenses in Indonesia: Between Legal Sanctions and Criminological Prevention - Pandapotan Damanik; Elpina; Van Lodewijk Purba; Zepa Frado Alexander Sinaga (KOLABORASI: Journal of Multidisciplinary, 2025)
Fencing, etymologically, derives from the word "tadah," which means a place to collect something, whereas in criminal law, fencing is defined as the act of receiving or collecting goods obtained from a crime with the intention of gaining profit, whether by purchasing, renting, exchanging, pawning, receiving as a gift, selling, leasing, storing, or concealing such goods, making the person who engages in these actions known as a fence or a receiver, which in the context of criminal law is a deliberate act committed by an individual or a group to gain benefit from items derived from crimes such as theft, fraud, or embezzlement, involving interaction not only with the victim but also with parties who assist or facilitate the crime, thus, this study aims to understand the crime of fencing from a criminological perspective, examine efforts to tackle this criminal act, and analyze the criminal liability imposed on the perpetrator, using a library research method for data collection, where the findings indicate that efforts to counter fencing crimes can be carried out through two means, namely penal and non-penal approaches, with the penal approach being legal actions taken through judicial channels, while the non-penal approach focuses on social strategies to mitigate the causes of crime, meanwhile, the criminal liability of fencing perpetrators is regulated under Article 480 of the Indonesian Criminal Code (KUHP), which imposes a maximum imprisonment of four years or a fine of up to nine hundred rupiahs on anyone who buys, rents, exchanges, pawns, receives as a gift, profits from, sells, leases, stores, or conceals goods that are known or reasonably suspected to have been obtained from a crime, as well as on anyone who benefits from goods known or reasonably suspected to have been acquired through criminal means.